Insect Stings and Bites: Teachers’ Knowledge of Prevention and First Aid Treatment regarding Allergies and Anaphylaxis in Primary Schools in Nigeria - Samuel Adesina Okueso; Victor Olusegun Adefarasin; Ademola Ridwan Adekola (Journal of Social Behavior and Community Health)
Background: Insects’ stings and bites are common phenomenon among school children in rural areas primarily due to closeness to bushes. Knowledge of teachers on allergies and anaphylaxis due to insect bites and stings is important to promote healthy school living; hence, this study investigated the knowledge of primary school teachers on stinging insects and allergic reactions. Methods: This was a descriptive survey research with 120 participants. Knowledge of insect stings prevention questionnaire (KISPQ r = 8.27) and knowledge of insect stings first aid treatment questionnaire (KISFATQ, r = 7.68) were the main instruments used for the study.  Mean and standard deviation were used to answer the four research questions while linear regression analysis was used to test the two postulated hypotheses at 0.05 alpha levels. Results: Findings revealed that teachers were not significantly knowledgeable about insects’ stings regarding allergies and anaphylactic reactions. This was because only about 50% of the teachers could recognize the insects causing allergies and anaphylactic reactions. The result of F-value of 81.760 whose probability was close to zero percent showed that, statistically, the teachers' knowledge of the prevention and first aid treatment of allergy due to insect bite had a significant influence on prevention of anaphylaxis. The result of F-value of 110.618 whose probability was close to zero percent indicated that teachers' knowledge of aetiology and prevention of allergy regarding insect bite had a significant influence on first aid skills. Conclusion: There is lack of knowledge in these areas at primary school level and that allergies and anaphylactic prevention should be added to health education curriculum content in school to improve knowledge of both the teachers and the pupils. Therefore, this study focuses on training teachers regarding prevention of insect stings and improving first aid treatment skills for stings and bites.